2021
DOI: 10.1155/2021/5530064
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Risk of Waste Pickers: A Case Study of Northern Region of South Africa

Abstract: In South Africa, waste pickers play a significant role in the management of waste at landfill sites. Waste picking is an income-generating venture for most people with low-income base. The activity of sorting waste at landfill sites is, however, associated with occupational health risks to waste pickers which this study has examined. The study adopted a cross-sectional survey with a convenience sampling method which was conducted among 114 waste pickers in three landfill sites in Limpopo Province of South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Moreover, health problems like hypertension, angina pectoris, myocardial infarction, chronic ischemic heart disease, heart failure, stroke, hemorrhoids, mono-neuropathy of the upper extremities, damage of the knee joint, back pain, synovitis and tenosynovitis, and other diseases of tendons and shoulder lesions were observed among street and SWCs ( 64 ). The other study conducted on waste collectors showed that dermatology or skin problems (10.53%), gastro-intestinal problems (7%), respiratory conditions (14.04%), musculoskeletal disorders (14.04%), eye problems (12.28%), and mental (21.05%) ( 65 ). Moreover, the prevalence of occupational injuries was 72.0%; musculoskeletal disorders (59.7%), respiratory symptoms (23.4%), head, eyes, and ears (7.8%), skin (5.2%), and gastrointestinal (3.9%) were common among waste collectors ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, health problems like hypertension, angina pectoris, myocardial infarction, chronic ischemic heart disease, heart failure, stroke, hemorrhoids, mono-neuropathy of the upper extremities, damage of the knee joint, back pain, synovitis and tenosynovitis, and other diseases of tendons and shoulder lesions were observed among street and SWCs ( 64 ). The other study conducted on waste collectors showed that dermatology or skin problems (10.53%), gastro-intestinal problems (7%), respiratory conditions (14.04%), musculoskeletal disorders (14.04%), eye problems (12.28%), and mental (21.05%) ( 65 ). Moreover, the prevalence of occupational injuries was 72.0%; musculoskeletal disorders (59.7%), respiratory symptoms (23.4%), head, eyes, and ears (7.8%), skin (5.2%), and gastrointestinal (3.9%) were common among waste collectors ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two third of the study participants are waste collectors and the remaining one third is street sweepers. The other the study conducted on waste collectors showed that Dermatology or skin problems (10.53%), Gastro intestinal problems (7%), Respiratory conditions (14.04%) and musculoskeletal disorders ((14.04%), eye problems (12.28%) and mental ((21.05%) (Uhunamure et al, 2021). Moreover, the prevalence of occupational injuries was 72.0%; musculoskeletal disorders (59.7%), respiratory symptoms (23.4%), head, eyes, and ears (7.8%), skin (5.2%) and Gastro Intestine (3.9%) were common among waste collectors (Sangkham et al, 2021).…”
Section: Multiple Occupational Related Studied Problemsmentioning
confidence: 98%
“…Many studies on the health impacts of waste picking focus on waste pickers who operate in landfills and dumpsites [ 13 , 22 , 23 , 24 , 25 ]. These offer important insights into occupational hazards and how to mitigate them.…”
Section: The Broader Context Of Waste Picking Health and Occupational...mentioning
confidence: 99%
“…Against the backdrop of these risks, however, waste pickers have low health-seeking behaviour [ 25 , 40 ]. All informal workers suffer from a ‘no work no pay’ situation, and this can make waste pickers reluctant to seek medical attention for work-related injuries.…”
Section: Occupational Hazards In the Inner Citymentioning
confidence: 99%